Implementasi Sistem Promosi Pejabat Struktural Di Sekretariat Daerah Kota Bitung - Damayanti, Eriska; Pangkey, Masje Silija; Kolondam, Helly (Sam Ratulangi University, 2016)
ABSTRACT: The process of structural official promotion can be seen still the employees who are not yetqualified rank is determined, the appropriate position, not yet qualified positions of seniority and experience.In the delivery of information only verbally, so it is still difficult to be accepted and understood by theintended object or the information. The purpose of this study was to determine the Structural PromotionSystem Implementation at the Regional Secretariat Bitung.Research using qualitative methods. The informants were 10 structural, staff / implementers. Datacollection by interview, while data analysis using interactive model analysis techniques. The focus of thestudy was defined as the implementation of a system of promotion or appointment / placement in a structuralposition as a civil servant which is already regulated in Government Regulation. Number 13 of 2002 on theappointment of civil servants in structural positions.The results showed: (1) policies (rules) is communicated or disseminated to employees, but notformally. Communication and coordination between the implementing unit managers pretty good. (2) Thedisposition is consistent implementation of regulations on the promotion system of civil servants in astructural position has been good, but not optimally. (3) implementing human resources policies areadequate, especially in BKD and Agency of office and rank position (Baperjakat). (4) The bureaucraticstructure / organization and job descriptions of the functions of the implementers of structural officerpromotion system is well defined, in which the selection process and the determination of structural officialsconducted by Baperjakat, while the technical and administrative processes implemented BKD.Keywords: Structural Promotion Policy Implementation